Indonesia : 2022 Article IV Consultation-Press Release; Staff Report; Staff Statement; and Statement by the Executive Director for Indonesia. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2022)
As elsewhere, the COVID-19 pandemic has led to tragic loss of life and triggered a major economic downturn in Indonesia. The authorities have responded with a bold and comprehensive policy package that has successfully maintained economic and financial stability. With the recovery underway, they have begun to withdraw the exceptional support measures. Nevertheless, the pandemic has caused scarring and reinforced the need to tackle longstanding structural challenges.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Indonesia